Correlation Between Changes in Environmental Temperature and Performance of High-Discharge Lithium-Polymer Batteries - Choi, Jaehun; Park, Heesung (Frontiers in Energy Research, 2022)
Electric vehicles (EVs) have been developed to solve environmental problems and the depletion of energy resources, and batteries have been used as their main energy source. The battery used in this study was a lithium polymer battery with the same chemical structure as lithium-ion. The use of a solid electrolyte has advantages, such as lack of leakage of electrolyte, high density per size, and convenient shape design. In this study, we analyzed the heat generation and performance characteristics of EV batteries through experiments on changes in environmental temperature. There is a difference in the heat generation depending on the discharge rate, and the performance characteristics of the battery improve as the environmental temperature rises. In the experiment, the battery performance was highest at an environmental temperature of 40 ℃, the critical heat generation at each discharge rate was 25.1 W, 81.0 W, and 151.5 W, and the efficiency was calculated as 88%. In this study, the heat generation and performance characteristics of the battery were analyzed according to the change in the environmental temperature and discharge rate of the battery, and it is inferred that it is an important factor that should be considered when configuring the cooling and heating system for optimal battery operation.